Pengaruh Investasi, Ekspor dan Impor terhadap Pertumbuhan Ekonomi Provinsi Jawa Timur Tahun 2017-2022 - Amadea Rachma Wati; Novi Khoiriawati (Universitas Batanghari Jambi, 2023)
This study aims to examine the effect of investment, exports and imports on the economic growth of East Java Province in 2017-2022. This research uses a quantitative approach with an associative type. The data used for research are investment, export, import, and GDP data obtained from the publication of the official website of DPMPTSP and BPS of East Java Province. This study used a purposive sampling technique, in order to obtain a sample of 36 based on 6 districts/cities in East Java Province in the 2017-2022 period. The data analysis technique of this study used panel data regression. The results of the study simultaneously show that investment, exports and imports have a significant effect on economic growth. While partially it is found that investment has a negative effect on economic growth, exports have a significant positive effect on economic growth, and imports have a significant negative effect on economic growth.